Strategi Pembelajaran Tematik melalui Pendekatan Interaktif Kelas II SDN Buaran Jati 2 Kecamatan Sukadiri - Magdalena, Ina; Syugaini, Joya; Nurvitasari, Nurvitasari (ALSYS, 2022)
Learning strategy is the process of selecting and arranging learning activities in a learning unit such as the sequence, nature of the material, scope of material, methods and media that are most appropriate to achieve learning competence. It is necessary to choose the right learning strategy in thematic learning, especially for low-grade children. Selection of appropriate learning strategies can facilitate students in achieving competence or learning objectives. The purpose of this study was to analyze the teacher's strategies used in thematic learning in class II SDN Buaran Jati 2. The results showed that teachers used learning strategies through an interactive approach. The research was conducted through observation by interviewing the principal and class teacher (class II) at SDN Buaran Jati 2. From the results of the interview, the teacher used an interactive approach with the aim of stimulating children to think creatively. The inhibiting factor is the child who is not good at socializing, therefore he is reluctant to respond to questions and ask questions so that the teacher must pay more attention which will make the child more confident.